Down-Regulation of P450 Genes Enhances Susceptibility to Indoxacarb and Alters Physiology and Development of Fall Armyworm, Spodoptera frugipreda (Lepidoptera: Noctuidae) - Hafeez, Muhammad; Li, Xiaowei; Ullah, Farman; Zhang, Zhijun; Zhang, Jinming; Huang, Jun; Fernández-Grandon, G. Mandela; Khan, Muhammad Musa; Siddiqui, Junaid Ali; Chen, Limin; Ren, Xiao Yun; Zhou, Shuxing; et al. (Frontiers in Physiology, 2022)
The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith), is a pest of many important crops globally. Effective control is challenging, with the pest exhibiting resistance to different synthetic pesticides across various groups. However, the mechanisms employed by resistant insects for overexpression of relevant detoxification genes remain unclear. The activity of detoxification enzymes was investigated in this study. Additionally, using RNA interference (RNAi), a functional analysis was completed of two P450s genes in an indoxacarb resistant population of fall armyworms. Elevated resistance levels (resistance ratio=31.37-fold) in indoxacarb-selected populations of FAW were observed after 14 generations. The qRT-PCR showed higher expression of two cytochrome P450 genes, CYP321A7 and CYP6AE43, in this selected population compared to the control population. RNAi was applied to knock down the P450 dsCYP321A7 and dsCYP6AE43 genes in the FAW larvae. Droplet feeding of the dsRNAs (CYP321A7 and CYP6AE43) via an artificial diet significantly increased mortality rates in the indoxacarb treated population. A shorter larval developmental time of FAW was detected in all dsRNAs-fed larvae. Correspondingly, larval mass was reduced by dsRNAs in indoxacarb resistant populations of fall armyworm. Larval feeding assays demonstrate that dsRNAs targeting, specifically of CYP321A7 and CYP6AE43 enzymes, could be a beneficial technique in the management of indoxacarb resistant populations. Further study on the potential use of dsRNA and its application should be conducted in efforts to counter the development of resistance in FAW against various insecticides in the field.